2011
DOI: 10.5191/jiaee.2011.18201
|View full text |Cite
|
Sign up to set email alerts
|

A Professional Competency Development Model: Implications for Extension Educators

Abstract: Professional development refers to continuing education designed to enhance competencies, skills, and knowledge. There is a need for a professional development model based on the educational processes used by educators of adults. A professional competency development model was constructed from a study grounded on four educational process areas in Extension. In this study, 441 randomly selected Extension educators in the North Central Region of the United States participated through an online survey. The propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Competency is a measure of competencies mastering, and competencies are a means of describing the objects and the types of professional activities to be mastered in the process of a specialist training [1]. Many works analysis let us make the conclusion that a competence is a certain sphere or a circle of issues for an authorized person to solve [2,3,4].…”
Section: The Concept and And Methodology Of The Studymentioning
confidence: 99%
“…Competency is a measure of competencies mastering, and competencies are a means of describing the objects and the types of professional activities to be mastered in the process of a specialist training [1]. Many works analysis let us make the conclusion that a competence is a certain sphere or a circle of issues for an authorized person to solve [2,3,4].…”
Section: The Concept and And Methodology Of The Studymentioning
confidence: 99%
“…Competencies for evaluators include a broad taxonomy including professional practice, systematic inquiry, social science research methods, situational analysis, project management, and reflective practice (Conner et al, 2013;Kock & Weeks, 2015;Shinn et al, 2009;Stevahn et al, 2005). Ghimire and Martin (2011) reported that extension staff require skills in assessing learning experiences and outcomes, evaluating program results, assessing program impacts, and using impact data for planning future programs.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…NGO and extension staff should possess program planning, needs assessment, and evaluation skills to be effective in their roles (Shinn, Wingenbach, Briers, Lindner, & Baker, 2009;Strong & Harder, 2011). Gaining M&E skills is a process of formal education, on-the-job training, and support from employers through evaluation capacity building continuing education (Ghimire & Martin, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For objective 3, the perceived level of importance and self-rated level of competency for core competencies are the dependent variables. The existing literature (Brodeur, Higgins, Galindo-Gonzalez, Craig, & Haile, 2011;Eicher, 2006;Ghimire & Martin, 2011;Lahai, Goldey, & Jones, 1999;Lopokoiyit, Onyango, & Kibett, 2013;Okwoche et al, 2011;McClure, Fuhrman, & Morgan, 2012) was used as the basis for selecting the explanatory variables. Though the literature suggests that the core competencies of EPs differ by those demographic traits listed above, there is no agreement on how they differ.…”
Section: Explanation Of Variablesmentioning
confidence: 99%